Engineering solutions to improve conditions and smoothness of train traffic on turnout switches - Boris E. Glyuzberg; Pavel V. Tregubchak; Il'ya V. Tsittser (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The currently used turnout switches geometries provided for the development and serial production of the main types of turnout equipment that ensure the transport process on the Russian railways. Further development of the infrastructure and the turnout facilities as its most important component calls for new, more advanced turnout switches geometries that take into account higher requirements for train speeds, dynamic loads and passenger comfort. The study develops geometries for the most common turnout equipment.Materials And Methods. The conditions of rolling stock movement along turnout switch are evaluated in terms of associated kinematics: travelling speeds, accelerations and the change rate of these accelerations. The developments in this article are based on the analysis of the cab kinematics moving along straight and branch tracks of turnout switches considering their properties and differences from the movement along curves on space intervals.Results. The proposed turnout switches have obtained data on unbalanced acceleration, energy loss, equivalent design speed and others. The paper offers design solutions to change turnout switches geometries that affect passenger comfort and provided the basis for the design of turnout geometries with a smoother rolling stock run.Discussion and Conclusion. An analysis of turnout switches geometry developments that smoothen rolling stock movement on turnout switches and improve passenger comfort identifies four engineering solutions recommended for implementation as providing the highest efficiency at the lowest cost of installation and operation on the Russian railway network. These are two variants of 1/11 turnout switches with tangent switch curves interchangeable with the turnout switches currently widely used on Russian railways, and two more gentle variants of 1/13 turnout switches. The engineering solutions developed under the same methodology are also recommended for 1/9 and symmetrical 1/6 turnout switches.